2023
DOI: 10.1371/journal.pone.0276356
|View full text |Cite
|
Sign up to set email alerts
|

Progression of chronic kidney disease among black patients attending a tertiary hospital in Johannesburg, South Africa

Abstract: Background Chronic kidney disease (CKD) is a major public health issue worldwide and is an important contributor to the overall non-communicable disease burden. Chronic kidney disease is usually asymptomatic, and insidiously and silently progresses to advanced stages in resource limited settings. Methodology A prospective longitudinal study was carried out on black patients with CKD attending the kidney outpatient clinic at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) in South Africa, between Sept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(80 reference statements)
0
3
1
Order By: Relevance
“…This study evaluated the prevalence, risk factors and outcomes of CKD progression among adult patients attending tertiary hospitals in Dodoma, Tanzania. In this study, the prevalence of CKD progression was 28.0% which is a lower than the reported prevalence of 51.5% in a population-based cohort in Canada, 49.5% among black patients in South Africa, 46.7% in a UK cohort study and 38% in a study conducted in northern California in USA (17)(18)(19)(20). We found a high prevalence of CKD progression than other studies; in the DISCOVER Trial it was reported to be 15.7%, in German CKD clinics it was reported to be 17% (16, 44).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…This study evaluated the prevalence, risk factors and outcomes of CKD progression among adult patients attending tertiary hospitals in Dodoma, Tanzania. In this study, the prevalence of CKD progression was 28.0% which is a lower than the reported prevalence of 51.5% in a population-based cohort in Canada, 49.5% among black patients in South Africa, 46.7% in a UK cohort study and 38% in a study conducted in northern California in USA (17)(18)(19)(20). We found a high prevalence of CKD progression than other studies; in the DISCOVER Trial it was reported to be 15.7%, in German CKD clinics it was reported to be 17% (16, 44).…”
Section: Discussioncontrasting
confidence: 61%
“…The risk factors associated with CKD progression include; hypoalbuminemia, proteinuria, increased LDL, diabetes mellitus, hypertension, and CKD stage (21,22). Studies have also reported younger age, male sex, African ancestry, current smoking, hypocalcaemia, high systolic blood pressure, elevated HbA1c, hyponatraemia, anaemia and heart failure as risk factors for CKD progression (19,23,24). Outcomes of CKD progression are generally poor as they are associated with increased morbidity and mortality ranging from cardiovascular diseases (CVDs), ESRD, frequent hospitalization and poor quality of life (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of CKD in this region has been estimated to be between 13.9 [ 4 ] 17.7% [ 5 ], exceeding the reported global average of 9.1% [ 1 ]. A complex interplay of genetic and socio-economic factors contribute to the increased risk of CKD development and progression in individuals of Black African ethnicity [ 6 , 7 ]; accelerated onset of kidney failure (KF) has been reported in South African series [ 8 ].…”
Section: Introductionmentioning
confidence: 99%